Determination of Hydrogeochemistry, Drinking and Irrigation Properties of Groundwaters in the Northwest Section of Afyon Plain - Can Başaran; Hüseyin Manap (Doğal Afetler ve Çevre Dergisi, 2023)
The water points located in the northwest part of the Afyon Plain are used as mains and irrigation water, by approximately 8000 people approximately 56 km2 of agricultural land. In order to use water resources effectively and efficiently, it is necessary to know the physical, chemical properties and the qualities of the waters very well. For this purpose, 12 groundwater were sampled within the scope of the study, and the hydrgeoochemical processes that gave the current compositions of the waters were determined, the analysis results were compared with the standards, and the irrigation water quality was Electrical conductivity (EC), Schoeller and Wilcox Diagram, Sodium Hazard (%Na and SAR), Residual Sodium Carbonate. (RSC), Magnesium Ratio (MR), Potential Salinity (PS) and Kelley index (KI) were interpreted using parameters. According to the analysis results, it was determined that the major cations of the waters were Ca, Mg and Na, and the major anion was HCO3. The schists and carbonate rocks cropping out in the region affect the current composition of the waters. However, the elements such as nitrate, arsenic, fluorine and boron, detected at some water points and exceeding the limit value may originate from domestic-agricultural wastes and fertilizers. The sampled waters should be used carefully and necessary precautions should be taken in terms of drinkability and irrigation water characteristics.